Trade-off between foliage and tuber resistance to Phthorimaea operculella in wild potatoes - Horgan, Finbarr G.; Quiring, Dan T.; Lagnaoui, Aziz; Pelletier, Yvan (Wiley, 2009)
Plants allocate resources between defence, reproduction, maintenance, and growth. This can lead to detectable allocation and ecological costs expressed as trade‐offs between distinct plant functions. It could also lead to trade‐offs between a plant's defences to different kinds of herbivores or a plant's defences to herbivory on different plant parts. We examined the hypothesis that allocation to defence in leaves is inversely related to allocation to defence in tubers of two distinct trichome‐bearing morphotypes of the wild potato, Solanum berthaultii Hawkes (Solanaceae). This species has been widely used in potato breeding programs aimed at acquiring foliage resistance to Phthorimaea operculella Zeller (Lepidoptera: Gelechiidae) and other herbivores. Phthorimaea operculella lays eggs in the soil and neonate larvae generally initiate host attack. We exposed leaves and tubers from multiple wild potato populations to neonate P. operculella. For both plant morphotypes, survival of neonate larvae placed on foliage was negatively correlated with the survival of neonate larvae placed on tubers, suggesting a trade‐off between the levels of herbivore defence in these plant tissues. These results suggest that the evolution of tuber resistance and trichome‐mediated foliage resistance to herbivores may not be independent, and that potato‐breeding programs that select for resistance in one tissue might compromise resistance in another.